Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Understanding innovation, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phen omena. They continue with an exploration of tools which can help impro ve the adaptive expertise needed for design thinking. The final part o f the book concerns design thinking in information technology and its relevance for business process modeling and agile software development , i.e. real world creation and deployment of products, services, and e nterprise systems"–Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations